Comparing Predictors of Intention for Physical Activity Participation between Normal and Overweight Military Spouses. Issue 4 (4th July 2022) - Speed, Shannon; Branscum, Paul; Gresla, Alice
ABSTRACT: Background: The Department of Defense (DOD) annually spends billions in medical care for military beneficiaries. Overweight and obesity are top concerns for dependents. Only 44% of military spouses (86% female, ages 25 to 34) meet Healthy People 2020 weight/BMI goals. Physical activity (PA) is an important modifiable behavior for preventing and treating obesity. The Theory of Planned Behavior (TPB) is a behavior change model that has been used in predicting PA behaviors. Purpose: The purpose was to evaluate theory-based determinants of aerobic and muscle-strengthening PA among female military spouses. Methods: Participants were recruited via social media to complete a modified version of an online survey measuring TPB constructs for aerobic and muscle strengthening PA. Results: Regression models showed TPB constructs predicted significant variance of intentions to engage in PA (44.9% to 52.1%) for normal weight and obese/overweight military spouses. Discussion: Results indicate interventions should differ by normal weight and overweight/obese due to differences in predictors of PA. Translation to Health Education Practice: Future research should test these findings in experimental studies evaluating the effectiveness of intervention to create PA adherence based on weight status of military spouses and at multiple levels of the ecological to understand how the environment influences. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars